Project Complexity Assessment and Management Tool. (2016) - Dao, Bac; Kermanshachi, Sharareh; Shane, Jennifer; Anderson, Stuart
Abstract: Project Complexity Assessment and Management (PCAM) Tool was developed to help project teams identify, assess, and manage project complexity. This Excel-based tool was designed with a "Complexity Measurement Matrix" comprising of the indicators that are statistically significant to project complexity. The weight factors of these complexity indicators were developed based on the expert ranking result from a subject matter workshop. These factors function as the multipliers to place greater emphasis on the stronger complexity indicators. The comprehensive reports from the tool present the overall project complexity level, a series of radar diagrams describing the most important indicators, and associated management strategies. The outputs help project teams formulate a management plan for the most important contributors with sufficient flexibility to be deployed at multiple project stages and for different project sizes.